A strong version of Poisson summation - Nelson Petulante (International Journal of Mathematics and Mathematical Sciences)
We establish a generalized version of the classical Poisson summation formula. This formula incorporates a special feature called compression, whereby, at the same time that the formula equates a series to its Fourier dual, the compressive feature serves to enable both sides of the equation to converge.